Inglés Incidence of tactical formations on the results of soccer matches played at altitude - Oscar Homero Valencia-Aguirre; Wilson Hernando Bravo-Navarro; Lenin Esteban Loaiza-Dávila; Mistral Homero Valencia-Cárdenas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: The Ecuadorian Professional Soccer League is a tournament that has teams that reside in cities at altitude and at sea level, for such reason the applied tactical formations differ with the objective of achieving a positive result when the encounter ends. Objective: To determine the incidence and effectiveness of the tactical formations applied in the results of soccer matches played in cities at altitudes between 2500 and 3250 meters above sea level. Method: Non-experimental quantitative study of correlational approach, in a study sample of 123 soccer matches played between 2020 and 2021 under these conditions, analyzed through the Instat Scout platform and the opinion of experts to determine the tactical formations of visiting teams residing at sea level, taking into account the effectiveness of points and goals obtained. Results: There were no differences between the means of goals scored and goals conceded by tactical formation; however, at a descriptive level, there was evidence of greater effectiveness in the 4-3-3 tactical formation due to the number of matches analyzed in relation to a higher mean of goals scored and a lower mean of goals conceded; statistically, there was a high positive correlation between the 1-3-4-3 tactical formation and goals scored with a significance level of P<0.01. Conclusion: The data obtained shows that the formations that use a line of 4 defenders obtain better results in comparison with the formations that use only 3 defenders, being the 1-4-3-3-3 tactical formation the one that obtained better results in contrast with the 1-3-5-2 formation that obtained the worst results.